Práticas algébricas no contexto da modelagem compreendida como proposta pedagógica - Posada Balvin, Fabian Arley [UNESP] (2015)
We analyzed the algebraic practices constructed by a group of students while they were developing modeling activities. The participants were students from a course of the Applied Mathematics program for Biology and Ecology of the UNESP - Rio Claro campus, that were invited to make a modeling project in any topic of their own interest as a part of the assignments of the course. This is a qualitative research where data were produced and analyzed from the historical and cultural perspective of the Theory of Activity, that presents the concept of practical activity as an explicative principle of the human development and focuses its attention mainly in three aspects: the mediation of cultural artifacts, the intersubjective relations and the conditions of the legitimation of the developed actions. According to the relationship patterns materialized in the mathematic models used, it was possible to conclude that among the discussed strands of mathematical practices related with the algebraic knowledge, the ones constituted by the students configured modes of action that take the concept of combined variation between different quantities (covariance), as principal unit analysis; that is, they adopt the variational or functional approach as a development principle. Although this type of mathematical practice deals with some level of generality, we emphasize in the need to generate actions for the spatiotemporal separation of the context in which they appeared, to be able to enter the field of the meaning of the algebraic knowledge. This means that the significant quantities have to go through a de-timing and despacialisation process, for them to be institutionalized in algebraic practice field; that is, for the modes of action of the subjects to be oriented to operate analytically with general relations among indeterminate amounts (variables, unknowns, parameters and generalized numbers). The results indicate that the processes of ...